2019
DOI: 10.3390/ijerph16234691
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Biogenic Secondary Pollution Materials from Sludge in Surface Waters

Abstract: Many countries of the world, including Lithuania, are making an effort to reduce surface water pollution. State monitoring data show that almost 80% of the lakes in Lithuania have an increased amount of sludge. One of the reasons for this increase in sludge is an excessive amount of biogenic material in the water. It is known that even after the source of pollution is removed, the condition of the lake water does not improve; rather, the condition of the lake water worsens due to the secondary pollution of slu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The linear regression equations developed can be used to calculate the correlation between the value of water quality indicators and water depth. The research showed that increasing the depth of the lake, can improve the ecological status of the lake by all indicators measured [45].…”
Section: Relation Of Hydromorphological Indicators With Hydrochemicalmentioning
confidence: 94%
See 1 more Smart Citation
“…The linear regression equations developed can be used to calculate the correlation between the value of water quality indicators and water depth. The research showed that increasing the depth of the lake, can improve the ecological status of the lake by all indicators measured [45].…”
Section: Relation Of Hydromorphological Indicators With Hydrochemicalmentioning
confidence: 94%
“…The results are presented in Figure 4. The research showed that increasing the depth of the lake, can improve the ecological status of the lake by all indicators measured [45].…”
Section: Relation Of Hydromorphological Indicators With Hydrochemicalmentioning
confidence: 94%
“…In many countries, large amounts of resources have been dedicated to the elimination of pollution sources. However, Česonien ė et al [7] found that the removal of pollution sources does not necessarily improve the quality of lake water because secondary pollution caused by sludge in the water can worsen the quality.…”
Section: Introductionmentioning
confidence: 99%